Health-Related Quality Of Life in Children with Cerebral Palsy in Low- and Middle-Income Countries: Opportunities and Next Steps - Angelina Kakooza, Mwesige (Dev Med Child Neurol, 2018)
Over recent decades, children with cerebral palsy (CP) are living longer than ever before, prompting researchers from several high-income countries (HICs) to explore the relationship of health with quality of life. In contrast, in the low- and middle-income countries (LMICs) where the burden of CP is higher compared to that in HICs and notably decreases with advancing age,1 there is hardly any information on this subject. The data from the few studies available reported very poor outcomes in comparison to those in HICs, and particularly in the aspect of physical well-being.2 These findings are disturbing but not surprising in view of the complexity of challenges which affect CP care and management in LMICs,3 coupled with the limited access to assistive technology for mobility.